Efficient Hybrid Tandem Solar Cells Based on Optical Reinforcement of Colloidal Quantum Dots with Organic Bulk Heterojunctions. Issue 7 (13th January 2020) - Aqoma, Havid; Imran, Imil Fadli; Mubarok, Muhibullah Al; Hadmojo, Wisnu Tantyo; Do, Young Rag; Jang, Sung‐Yeon
Abstract: While colloidal quantum dot photovoltaic devices (CQDPVs) can achieve a power conversion efficiency (PCE) of ≈12%, their insufficient optical absorption in the near‐infrared (NIR) regime impairs efficient utilization of the full spectrum of visible light. Here, high‐efficiency, solution‐processed, hybrid series, tandem photovoltaic devices are developed featuring CQDs and organic bulk heterojunction (BHJ) photoactive materials for front‐ and back‐cells, respectively. The organic BHJ back‐cell efficiently harvests the transmitted NIR photons from the CQD front‐cell, which reinforces the photon‐to‐current conversion at 350–1000 nm wavelengths. Optimizing the short‐circuit current density balance of each sub‐cell and creating a near ideal series connection using an intermediate layer achieve a PCE (12.82%) that is superior to that of each single‐junction device (11.17% and 11.02% for the CQD and organic BHJ device, respectively). Notably, the PCE of the hybrid tandem device is the highest among the reported CQDPVs, including single‐junction devices and tandem devices. The hybrid tandem device also exhibits almost negligible degradation after air storage for 3 months. This study suggests a potential route to improve the performance of CQDPVs by proper hybridization with NIR‐absorbing photoactive materials. Abstract : High‐efficiency, solution‐processed, hybrid tandem photovoltaic devices are demonstrated employing colloidal quantum dot (CQD) and organic bulk heterojunction as an active layer for front‐ and back‐cell, respectively. Notable efficiency of 12.82% is achieved, which is the highest among the reported CQD‐based solar cells, including single‐junction devices and tandem devices.